Determination of perceptual boundaries between the male, female and child's voices in isolated synthethic Polish vowels - J. IMIOŁCZYK (Archives of Acoustics)
The problem of perceptual boundaries between the male, female and child's voices was considered. The experimental material included 730 synthetic realisations of the six Polish oral vowels: /i/, /i/, /e/, /a/, /o/ and /u/. "Target" male, female and child's utterances as well as a number of intermediate ones were obtained for each vowel by selecting appropriate combinations of FO and formant frequency values. Results of the listening test show that FO is the principal factor determining the perception of voice category and that, as such, it plays the key role in the perceptual normalisation of the speaker's vocal tract.